Розроблення електричної моделі вулично-дорожньої мережі для аналізу і оптимізації транспортних потоків у містах - Тарабан, Сергій (Посвіт, 2019)
In the paper is shown the peculiarities of the proposed method of electric simulation the structural configuration of the urban road network. Each section of the urban road network is simulated by a serial connection of the diode and the resistance. This allows the electric circuit to reflect the parameters of the configuration of the structural elements of the urban road network and the traffic organization on the network.
Development of electrical model of an urban road network for analysis and optimization of traffic flows in cities
Keywords: 656.11